Simulation-Based Interpretation of Therapeutically Monitored Cabozantinib Plasma Concentration in Advanced Adrenocortical Carcinoma with Hemodialysis. Issue 5 (October 2021) - Zimmermann, Sebastian; Kurlbaum, Max; Mayer, Stefanie; Fassnacht, Martin; Kroiss, Matthias; Scherf-Clavel, Oliver
Abstract : Background: Adrenocortical carcinoma is an orphan but aggressive malignancy with limited treatment options. Cabozantinib (CAB), a tyrosine kinase inhibitor, has emerged as a new potential treatment. However, no data are available on whether and how CAB can be administered to patients undergoing hemodialysis. Methods: An liquid chromatography with tandem mass spectrometry detection method was developed and validated according to the European Medicines Agency and United States Food and Drug Administration guidelines for bioanalytical method validation. The samples were prepared using protein precipitation and online solid-phase extraction. The method was applied to clinical samples of an adrenocortical carcinoma patient receiving CAB treatment (80 mg daily). During the 10 days of observation, the patient received periodic hemodialysis on 7 days. Pharmacokinetic (PK) simulations were performed using Bayesian forecasting according to an existing population PK model for CAB. Results: Based on the PK simulation, a mean plasma trough concentration of 1375 ng/mL [90% prediction interval (PI), 601–2602 ng/mL] in the steady state at a daily dose of 80 mg was expected for CAB. However, an individual simulation involving the measured plasma levels of the patient resulted in a mean trough concentration of 348 ng/mL (90% PI, 278–430 ng/mL). The model based on individual PK parameters estimated accessible plasma levels of 521, 625, and 834 ng/mL by dose adjustment to 100, 120, and 160 mg, respectively. Conclusions: After establishing an liquid chromatography with tandem mass spectrometry detection method for therapeutic drug monitoring of CAB, our analyses involving a single patient undergoing hemodialysis indicated that higher than expected doses of CAB were required to achieve reasonable plasma concentrations. Our study demonstrates the usefulness of therapeutic drug monitoring for the evaluation of "new" drugs in patients with renal impairment. Abstract : Supplemental Digital Content is Available in the Text.